PENGUKURAN KEY PERFORMANCE INDICATOR SISTEM MANAJEMEN GUDANG DI PERUSAHAAN LOGISTIK - Hendrawan Suryajaya; Wilson Kosasih; Carla Olyvia Doaly; Lithrone Laricha Salomon (Jurnal Ilmiah Teknik Industri, 2025)
Many sellers of goods through digital platforms (marketplaces) do not have large storage space, so currently logistics companies also provide warehouse services to store goods from these sellers. A good warehouse management system (WMS) must be able to flow goods from input to output effectively and efficiently. Many logistics companies have yet to comprehensively measure key performance indicators (KPIs) for their WMS due to the perception that measurement is difficult and should only be performed by experts. This study aims to design and measure the KPIs of a WMS. This study uses a case study approach in a logistics company that has a storage area for various types of goods from sellers. Data were collected through literature studies, observations, and interviews. The methods used were the Analytical Hierarchy Process (AHP) and Snorm De Boer. The results show that three KPIs fall into the poor category, including: putaway per man-hour, % location and cube occupied, and order lines picked per man-hour. The company needs to create a structured system for storing goods based on their type, set standard storage time limits or even increase storage capacity, and also need to monitor the smooth flow of goods. In the end, it is hoped that all proposed KPIs can be measured periodically for continuous improvement.